Developing rugby in interwar Romania: the case of provincial cities and towns. Issue 2 (2nd April 2020) - Rotar, Marius
ABSTRACT: The growth in interest for the historical analysis of sports in Romania has lately been focusing more on general issues or on the major sports (for instance, football). As a result, despite its early apparition in Romania (1913), and its development in comparison with other Central European countries, Rugby has been completely ignored. The aim of this article is to analyze the ways in which the development of the sport was attempted in Interwar Romania. This is a case study focused on the efforts to popularise rugby in the towns outside of Bucharest, the capital of Romania. These efforts were administered in a combination of two ways: the propaganda rugby matches in different cities and the organisation of rugby teams in provincial cities and were based more on individual actions rather than the coordinated action of the Romanian Rugby management of those times. The conclusions emphasise the minor success of this initiative, contextualising it in the rugby and sports' condition in Interwar Romania.